ANALISIS KEAKTIFAN BELAJAR SELAMA PEMBELAJARAN DARING PADA MASA COVID-19 DI MIN 19 ACEH SELATAN - Irwandi (FITRAH was published by the Center for Research and Community Service (LP2M) Ar-Raniry Islamic State University Banda Aceh, 2021)
This research is a field research conducted in MIN 19 South Aceh Regency. The author's background in conducting this research is that due to the COVID-19 pandemic that is engulfing all parts of the world, including Indonesia and Aceh, learning activities since March 2020 are no longer carried out face-to-face, but follow the government's recommendation, namely through online learning. The purpose of this study was to determine the activeness of the learning process through online learning during the covid-19 period at MIN 19 Aceh Selatan. Then to find out the inhibiting factors for the learning process through online learning during the covid-19 period at MIN 19 South Aceh. And to find out the efforts made in overcoming the obstacles of online learning at MIN 19 South Aceh. The method used in this study is a qualitative method with data collection techniques, namely by means of observation, documentation and interviews. The results of the study indicate that online learning at MIN 19 Aceh Selatan is less active due to obstacles in the form of students not focusing on the online learning system, lack of online learning facilities such as the internet and so on, then also unprepared parents and teachers in dealing with learning. the online. The effort to overcome these obstacles is by the government providing adequate facilities to schools, and parents and teachers must prepare themselves with all the learning needs of students in the modern era.